Pulmonary arteriovenous fistula within a pulmonary cyst – evaluation with CT pulmonary angiography - Ghersin, E (The British Institute of Radiology., 2010)
Pulmonary arteriovenous malformations (PAVMs) are abnormal direct communications between pulmonary arteries and pulmonary veins. These abnormal communications result in an anatomical right-to-left shunt that reduces the arterial oxygen saturation and may cause hypoxaemia and dyspnoea. Although PAVMs frequently remain undiagnosed, they are associated with severe morbidity in the form of ischaemic strokes and brain abscesses. We report a case of incidental CT angiography depiction of a PAVM within a pulmonary cyst. To the best of our knowledge, no such case has been described previously. On the basis of its appearance and lack of typical clinical features of hereditary haemorrhagic telangiectasia (HHT), we suggest that this PAVM actually represents an acquired fistula from a previously unrecognised focal pulmonary insult, such as trauma or infection, that simultaneously evolved into a pulmonary arteriovenous fistula (PAVF) within a traumatic pulmonary cyst or pneumatocele.